1994
DOI: 10.1523/jneurosci.14-12-07695.1994
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of myosin light chain kinase in the mechanism for MgATP- dependent priming of exocytosis in adrenal chromaffin cells

Abstract: Ca(2+)-induced exocytosis in chromaffin cells now seems to consist of at least two distinct steps:MgATP-dependent Ca(2+)-dependent priming of the secretory apparatus, and Ca(2+)-dependent MgATP-independent step that triggers exocytosis (Bittner and Holz, 1992). Recently we found that a specific inhibitor of myosin light chain kinase (MLCK), wortmannin, inhibits Ca(2+)-induced catecholamine release from digitonin-permeabilized chromaffin cells, suggesting an implication of MLCK in the mechanisms of Ca(2+)-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 51 publications
4
42
0
Order By: Relevance
“…Myosin light chain kinase, which is a key regulator of myosin II, has also been implicated in vesicle release at neural synapses ( 22 ) and the ATP-dependent priming of exocytosis in chromaffi n cells ( 23 ), further indicating that myosin II may play a key role in vesicle fusion.…”
Section: Cells and Inhibitorsmentioning
confidence: 99%
“…Myosin light chain kinase, which is a key regulator of myosin II, has also been implicated in vesicle release at neural synapses ( 22 ) and the ATP-dependent priming of exocytosis in chromaffi n cells ( 23 ), further indicating that myosin II may play a key role in vesicle fusion.…”
Section: Cells and Inhibitorsmentioning
confidence: 99%
“…Acetylcholine-SNAP and NSF were also shown to increase the priming rate (Xu et al, 1999). Several kinases such as PKA, protein kinase C (PKC), Ca 2ϩ -regulated myosin light chain kinase have been shown to modulate neurotransmitter release (Kumakura et al, 1994;Capogna et al, 1995;Mochida, 1995). Finally, PtdIns(4,5)P 2 formation by the conjoint ATP-dependent activities of PI4K and PI4P5K has been shown to be required for LDCV priming (Martin et al, 1997) In contrast to its role in signal transduction, where it acts as a substrate for the generation of diacylglycerol and InsP 3 , PtdIns(4,5)P 2 itself is likely to serve as a membrane anchor or modulator for several proteins of the secretory apparatus, such as synaptotagmins and CAPS (Walent et al, 1992;Schiavo et al, 1996).…”
Section: Involvement Of Pi3k-c2␣ Enzymatic Activity In Neurosecretionmentioning
confidence: 99%
“…However, the e ective concentration range of wortmannin for inhibiting the release of SP from cultured DRG neurons was higher than that inhibiting PI3-kinase. Furthermore, wortmannin showed similar IC 50 values (approximately 1 mM) for inhibition of the release of catecholamines in both intact and permealized chroma n cells (Ohara-Imaizumi et al, 1992;Kumakura et al, 1994), suggesting that cell membranes do not hamper the penetration of wortmannin to the interior of neurons. Taken together, the e ect of wortmannin in the present study suggests that phosphorylation of myosin II plays an important role in the release of SP.…”
Section: Discussionmentioning
confidence: 93%
“…The anti-SP antibody was also reported to react speci®cally with SP in the rat spinal cord (Cuello et al, 1979), but not with other peptides such as Leuor Met-enkephalin (see manufacturer's product description). Characterization of the anti-myosin II rabbit antibody was described elsewhere (Kumakura et al, 1994;Mochida et al, 1994). Immunoblotting of homogenates from various kinds of tissues including nervous system showed that the antibody binds to a single band of 200 KDa, which corresponds to the molecular weight of mysoin II heavy chain.…”
Section: Immuno¯uorescent Experimentsmentioning
confidence: 99%
See 1 more Smart Citation